Cirque de freak : the lake of souls - Shan, Darren (New York : Little, Brown, 2003)
The lives of Darren and Harkat are at risk as they face monstrous obstacles on a desperate quest to the Lake of Souls.
920
Accelerated Reader AR
Keywords: Vampires -- Fiction; Horror stories